Phenological growth stages of stevia (Stevia rebaudiana Bertoni) according to the Biologische Bundesanstalt Bundessortenamt and Chemical Industry (BBCH) scale. (24th August 2020) - Le Bihan, Zoé; Cosson, Patrick; Rolin, Dominique; Schurdi‐Levraud, Valérie
Abstract: Stevia ( Stevia rebaudiana Bertoni) is a perennial crop belonging to the Asteraceae family. Its main agronomic and industrial interest is the accumulation in its leaves of steviol glycosides (SG), natural acaloric sweeteners which are 300 times sweeter than sucrose. In order to expand phenotyping knowledge on this emerging crop, researchers and breeders need a universal scale to describe the development of this plant. The objective of this study was to describe the phenological growth stages of stevia through the use of the Biologische Bundesanstalt Bundessortenamt and Chemical Industry (BBCH) scale to provide a standard scale for stevia grown under temperate conditions of production and climate. The observation of phenological stages was performed on genetic resources and validated on stevia progenies grown in field conditions. The 10 phenological stages, namely germination, bud development, foliar development, side shoots appearance, stems elongation, development of harvestable part of the crop, inflorescence emergence, flowering, development of fruit, seeds ripening and senescence, were used to describe the stevia, supplemented with pictures. The chronology and duration of each stage were also observed and described according to the accumulation of degree days during the growing season. This study presents the first BBCH scale established for S. rebaudiana cultivated in temperate conditions and a chronology of phenological stages based on the accumulation of thermal time, through growing degree day calculation (°C/day). This work provides a tool that can be widely used by farmers, breeders and researchers leading to better agronomic management and scientific communication. Abstract : Stevia rebaudiana (Bertoni) is a perennial crop belonging to the Asteraceae family. Its main agronomic and industrial interest is the accumulation in its leaves of steviol glycosides, natural acaloric sweeteners. In order to expand phenotyping knowledge on this emerging crop, researchers and breeders need a universal scale to describe the development of this plant. This study establishes the first BBCH scale for stevia cultivated in temperate conditions and a chronology of phenological stages based on the accumulation of thermal time, through growing degree day calculation (°C/day). This work provides a useful tool for better agronomic management.